How do South Africans experience and respond to HIV stigma? - Ferreira, Cherie (My University, 2021)
Background: HIV (Human Immunodeficiency Virus) is a global pandemic that negatively effects a person’s physical and social health. The stigma and discrimination related to HIV has been well documented in previous research (Aggleton et al., 2004; Gilbert, 2016; Gilbert & Walker, 2010; Kimera et al., 2020; Link & Phelan, 2014; Parker & Aggleton, 2003; Scambler, 2009; Zuch & Lurie, 2012). Education has been one of the main tools used to combat the stigma related to HIV, as ignorance is viewed to be the main driver behind people’s stigmatizing attitudes towards people living with HIV (PLHVs). The discriminatory behaviour that has been informed by stigmatizing attitudes have also been well documented in previous research (Goffman, 1959, 1963; Hatzenbuehler et al., 2013; Link et al., 2004; Link & Phelan, 2014, 2001; Mill et al., 2013), however, stigma still exists (Mahamboro et al., 2020). Therefore, this research project set out to understand how South African PLHVs experienced and responded to HIV - related stigma. Purpose: The purpose of this research project was to understand how South African PLHVs experienced and responded to HIV-related stigma. Methods: To achieve the stated purpose, a qualitative research methodology was utilized that saw to the usage of one – on – one semi – structured interviews. The interviews were conducted with four HIV - positive women from the Princess Informal Settlement in Roodepoort. Ethical clearance was obtained from the Research Ethics Committee of the University of Witwatersrand. Verbal consent was obtained from all participants before the commencement of interviews. All interviews were audio recorded and manually transcribed in semi - verbatim. A thematic analysis was conducted on the transcripts in line with Braun and Clarke’s (2018) prescriptions. Results: In response to experienced stigma, this research project found that PLHVs employed impression management and self – isolation tactics. Additionally, it was also concluded that the education efforts within the community did address the issues of internalized stigma and acceptance among PLHVs close family members. Although the existing efforts did not address the stigmatizing attitudes that were prevalent within the wider community. Recommendations: The recommendations of this research report are that a more extensive, multitier education approach is needed to address the prevalent stigma within the community at large. Additionally, to address the issues of loneliness and shame among PLHVs, a pride march is recommended to assist PLHVs in building up their self-esteem and community solidarity. Finally, community solidarity would also be duly strengthened through the re-establishment of PLHV support groups within the P.I.S. community.
A research project submitted in partial fulfilment of the requirements for the degree of Masters of Arts by Coursework and Research to the Faculty of Humanities, School of Sociology, University of the Witwatersrand, 2021